C-index: A novel method to assess surgical morbidity in obstetric and gynecological surgery: A retrospective study - Chanil Deshan Ekanayake; Arunasalam Pathmeswaran; Sakshara Ranasinghe; Amritha Sridaran; Yeshmitha Madanayake; Samurdika Nishamalee (Journal of Clinical Sciences)
Background: There is a need to develop a method of assessing the outcomes of surgery that is as accurate as studying complications, more objective than patient-reported outcome measures and easier than cost-effective analysis. The C-index is proposed to assess the surgical outcomes instead of studying complications which require large sample sizes. Methods: A retrospective case series study included all patients who underwent major surgery in obstetrics and gynecology at a university hospital. The C-index was calculated as; C-index = (sum of intensive care unit [ICU] stay – sum of ICU stay ≤24-h) × 100/total major surgeries. Results: C-index for cesarean sections (n = 731) and gynecological surgery (n = 284) was 5.2 and 10.9 respectively. In terms of cesarean sections; ICU stay >24-h was increased by; total number of complications in a patient (P < 0.01, odds ratio [OR] = 3.04 [1.34–6.88]) and age (P < 0.05, OR = 1.15 [1.01–1.32]). In terms of gynecological surgery; ICU stay >24-h was increased by total complications in a patient (P < 0.001, regression coefficient = 1.70 [1.37–2.03)]). Conclusion: The ICU stay >24-h is related to total complications in a patient for both cesarean sections and gynecological surgery. Therefore, as the C-index is related to ICU stay >24 h, it offers an objective picture of surgical outcomes as accurate as assessing surgical complications, although in a more feasible way. The C-index is a universally acceptable tool to assess surgical morbidity in obstetric and gynecological surgery that can be easily calculated using minimal resources in any setting and offers a new dimension for quality control, risk management, and benchmarking using routinely available data.